Functioning and post‐school transition outcomes for young people with Down syndrome. Issue 6 (7th January 2013) - Foley, K.‐R.; Jacoby, P.; Girdler, S.; Bourke, J.; Pikora, T.; Lennox, N.; Einfeld, S.; Llewellyn, G.; Parmenter, T. R.; Leonard, H.
Abstract: Aim: To investigate the relationship between functioning and post‐school day occupation for young adults with Down syndrome. Methods: Families of young people with Down syndrome ( n = 269) aged 15–30 years in 2009 were recruited from the population‐based Down syndrome 'Needs Opinion Wishes' database in Western Australia. Questionnaires were mailed to participating families and involved two parts, young person characteristics and family functioning; 203 were returned (75%). Of those families who returned questionnaires, 164 (80.8%) of their young adults had left school. Participation in post‐school day occupations was the main outcome and included; open employment, training, sheltered employment or alternatives to employment (ATE). Results: Young adults were reported as participating in open employment ( n = 42), training ( n = 17), sheltered employment ( n = 64) or ATE ( n = 41) post‐school. Those who reported better functioning in self‐care, community and communication skills were more likely to be in open employment and/or attending Technical and Further Education compared with those attending sheltered employment and/or ATE after adjusting for age, gender and rural/metropolitan regions. Current health as measured by visits to a general practitioner (GP) and hospitalizations revealed a weak relationship with post‐school day occupations, with increasing likelihood of participating in open employment or training with increasing hospitalizations and GP visits. Conclusions: Our analysis shows that functioning in activities of daily living was related to post‐school day occupation. Current health status and behaviour were found to have a weak relationship with post‐school day occupation adjusting for functioning in the final model.